Physiological Role of Glutamate Dehydrogenase in Cancer Cells - Moreno-Sánchez, Rafael; Marín-Hernández, Álvaro; Gallardo-Pérez, Juan C.; Pacheco-Velázquez, Silvia C.; Robledo-Cadena, Diana X.; Padilla-Flores, Joaquín Alberto; Saavedra, Emma; Rodríguez-Enríquez, Sara (Frontiers in Oncology, 2020)
NH4+ increased growth rates and final densities of several human metastatic cancer cells. To assess whether glutamate dehydrogenase (GDH) in cancer cells may catalyze the reverse reaction of NH4+ fixation, its covalent regulation and kinetic parameters were determined under near-physiological conditions. Increased total protein and phosphorylation were attained in NH4+-supplemented metastatic cells, but total cell GDH activity was unchanged. Higher Vmax values for the GDH reverse reaction vs. forward reaction in both isolated hepatoma (HepM) and liver mitochondria [rat liver mitochondria (RLM)] favored an NH4+-fixing role. GDH sigmoidal kinetics with NH4+, ADP, and leucine fitted to Hill equation showed nH values of 2 to 3. However, the K0.5 values for NH4+ were over 20 mM, questioning the physiological relevance of the GDH reverse reaction, because intracellular NH4+ in tumors is 1 to 5 mM. In contrast, data fitting to the Monod–Wyman–Changeux (MWC) model revealed lower Km values for NH4+, of 6 to 12 mM. In silico analysis made with MWC equation, and using physiological concentrations of substrates and modulators, predicted GDH N-fixing activity in cancer cells. Therefore, together with its thermodynamic feasibility, GDH may reach rates for its reverse, NH4+-fixing reaction that are compatible with an anabolic role for supporting growth of cancer cells.